2017
DOI: 10.1002/pssb.201700291
|View full text |Cite
|
Sign up to set email alerts
|

Hexagonal Array of Mesoscopic HTM‐Based Perovskite Solar Cell with Embedded Plasmonic Nanoparticles

Abstract: Inorganic hole‐transporting materials (HTMs) profoundly improve the stability and robustness of the solar cell compared to that expected from organic HTMs. In this work, the efficiency of a perovskite solar cell is greatly enhanced using a hexagonal nanoprism array of inorganic metal oxide HTM. We found that the introduced structure increases the efficiency of the mesoscopic configuration by 42% higher than that of the planar perovskite solar cell with the same thickness of the active layers. The reason of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…To simulate optical properties of the PSC, we have to calculate the total optical absorption. It is computed as follows [18,21,22]:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To simulate optical properties of the PSC, we have to calculate the total optical absorption. It is computed as follows [18,21,22]:…”
Section: Methodsmentioning
confidence: 99%
“…The Au material has chemical stability in many environments and it is a suitable material in localized surface plasmon resonance (LSPR) applications. However, the easy oxidation of Ag upon air exposure can change its plasmonic properties which is why we used Au NPs in a simulation of the device [18]. In this work, we considered the influence of the number, position, volume, and spacing of the Au NPs from each other.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the EQE was enhanced, and the EQE improvement was slightly higher with Ag NPs than with Au NPs. E. Ghahremanirad et al theoretically demonstrated that the performance of planar PSCs was enhanced when HTL was a hexagonal NiO nanoprism array with Au NPs distributed in the gaps 89 . The calculations were based on the 3D FDTD method and the finite element method (FEM).…”
Section: Plasmonic–perovskite Solar Cellsmentioning
confidence: 99%
“…For example, a periodic array of hexagonal NiO x nanoprisms increased the efficiency of mp inverted n–i–p PSCs by 42% as it facilitated carrier transport. 230 Note that, similar to the role of a compact TiO 2 film, a compact NiO x film is generally highly effective in electron blocking and avoiding undesirable interfacial recombination in mp-NiO x based PSCs with ITO or FTO electrodes. Moreover, recent work has highlighted the working mechanism of alternatively incorporating a thin insulating mp scaffold Al 2 O 3 interlayer at the bottom electrode in both p–i–n and n–i–p mp structures unveiling the dependency of the perovskite electronic structure on its physical confinement with the mp scaffold and the overall improved interfacial band alignment.…”
Section: Hole Transport Materials In Mp-pscsmentioning
confidence: 99%